Cobalamin and microbial plankton dynamics along a coastal to offshore transect in the Eastern North Atlantic Ocean. (3rd January 2021) - Joglar, Vanessa; Álvarez‐Salgado, Xosé Antón; Gago‐Martinez, Ana; Leao, Jose M.; Pérez‐Martínez, Clara; Pontiller, Benjamin; Lundin, Daniel; Pinhassi, Jarone; Fernández, Emilio; Teira, Eva
Summary: Cobalamin (B12) is an essential cofactor that is exclusively synthesized by some prokaryotes while many prokaryotes and eukaryotes require an external supply of B12. The spatial and temporal availability of B12 is poorly understood in marine ecosystems. Field measurements of B12 along with a large set of ancillary biotic and abiotic factors were obtained during three oceanographic cruises in the NW Iberian Peninsula, covering different spatial and temporal scales. B12 concentrations were remarkably low (<1.5 pM) in all samples, being significantly higher at the subsurface Eastern North Atlantic Central Water than at shallower depths, suggesting that B12 supply in this water mass is greater than demand. Multiple regression models excluded B12 concentration as predictive variable for phytoplankton biomass or production, regardless of the presence of B12‐requiring algae. Prokaryote production was the best predictor for primary production, and eukaryote community composition was better correlated with prokaryote community composition than with nutritional resources, suggesting that biotic interactions play a significant role in regulating microbial communities. Interestingly, co‐occurrence network analyses based on 16S and 18S rRNA sequences allowed the identification of significant associations between potential B12 producers and consumers (e.g. Thaumarchaeota and Dynophyceae, or Amylibacter and Ostreococcus respectively), which can now be investigated using model systems in the laboratory.